The Effect of Mathematics Learning with the Creative Visualization Technique on the Geometry Ability Level of Students at SMP Islam Wonopringgo - Gangga Bramantya Pradana; Nalim, Nalim (STAI Al-Bahjah, 2024)
Students often face difficulties in understanding geometric concepts, particularly in the Pythagorean theorem as well as in plane and solid geometry, necessitating innovation in teaching methods. This study aims to examine the effect of problem-based mathematics learning using the Creative Visualization technique on improving the geometry skills of eighth-grade students at SMP Islam Wonopringgo, based on Van Hiele’s theory. The study employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two purposively selected classes: the experimental class, which received instruction using the Creative Visualization technique, and the control class, which followed conventional teaching. The research instrument was a geometry skills test based on Van Hiele's five levels of geometric thinking. The results showed a significant difference in the improvement of geometry skills between the two groups. Students in the experimental class showed more significant progress, particularly at the analysis and informal deduction levels. Thus, the Creative Visualization technique is proven to be effective in enhancing students’ geometry skills and can be considered an alternative method in geometry instruction.